MHC-DRB1/DQB1 Gene Polymorphism and Its Association with Resistance/Susceptibility to Cystic Echinococcosis in Chinese Merino Sheep. (24th March 2014) - Shen, Hong; Han, Guohua; Jia, Bin; Jiang, Song; Du, Yingchun
Abstract : The aim of this study was to analyze the relationship between polymorphism of the MHC-DRB1/DQB1 gene and its resistance to Cystic Echinococcosis (C.E), as well as to screen out the molecular genetic marker of antiechinococcosis in Chinese Merino sheep. The MHCII-DRB1/DQB1 exon 2 was amplified by polymerase chain reaction (PCR) from DNA samples of healthy and hydatidosis sheep. PCR products were characterized by restriction fragment length polymorphism (RFLP) technique. Five restriction enzymes (Mval, HaeIII, SacI, SacII, and Hin1I) were employed to cut DRB1, while seven restriction enzymes (MroxI, ScaI, SacII, NciI, TaqI, Mval, and HaeIII) were employed to cut DQB1.Results showed that frequencies of patterns Mvalbb (P < 0.01 ), SacIab in DRB1 exon 2 (P < 0.05 ), and TaqIaa, HaeIIInn (P < 0.01 ) in DQB1 exon 2 were significantly higher in the healthy group compared with the C.E individuals, which implied that there was a strong association between these genotypes and hydatidosis resistance or susceptibility. Chi-square test showed that individuals with the genic haplotype DRB1-SacIab/DRB1-Mvalbb/DQB1-TaqIaa/DQB1-HaeIIInn (P < 0.01 ) were relatively resistant to C.E, while individuals with the genic haplotypes DRB1-Mvalbc/DQB1-Mvalyy/DQB1-TaqIab/DQB1-HaeIIImn (P < 0.01 ) and DRB1-Mvalbb/DQB1-Mvalcc/DQB1-TaqIab/DQB1-HaeIIImn (P < 0.01 ) were more susceptible to C.E. In addition, to confirm these results, a fielding experiment was performed with Chinese Merino sheep which were artificially infected with E.g . The result was in accordance with the results of the first study. In conclusion, MHC-DRB1/DQB1 exon 2 plays an important role as resistant to C.E in Chinese Merino sheep. In addition, the molecular genetic marker of antiechinococcosis (DRB1-SacIab/DRB1-Mvalbb/DQB1-TaqIaa/DQB1-HaeIIInn) was screened out in Chinese Merino sheep.